Banjar Siam Orange Ice Cream: A Catalyst for Village Tourism - Arif Sholahuddin; Rusmansyah; Mahdian; Leny; Syahmani; Anisa; Aliman; Handi Al Fakhri; Muhammad Ismi Rezani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
The main challenge faced by the Karang Bunga Village community is the low price of Siam Banjar oranges during the harvest season, which negatively affects the farmers' economy. To address this issue, it is necessary to diversify processed citrus products as part of the Citrus House business unit managed by the Village-Owned Enterprise (BUMDes) "Berkah Bersama." This Community Service activity utilized the “service learning” method to train students in leadership skills through hands-on community empowerment efforts. One of the main focuses of the community service activity was developing an ice cream product made from Siam Banjar oranges, covering aspects such as production, packaging, and marketing. The results of the community service activity showed an increase in community skills and knowledge, with an average score of 2.99, indicating that the level of knowledge and skills falls within the "good" category. However, there are still challenges in the areas of packaging and marketing. The average score for the evaluation of the activity implementation was 3.42 (good category), and the average score for the resulting ice cream product was 3.13 (also in the good category). This activity is expected to improve product quality, expand market reach, and ultimately have a positive impact on the income of the village community.